1998
DOI: 10.1007/s005340050036
|View full text |Cite
|
Sign up to set email alerts
|

Solitary fibrous tumor of the liver with CD 34 positivity and hypoglycemia

Abstract: We report a new case of solitary fibrous tumor (SFT) of the liver, an extremely rare neoplasm. Including the present case no more than ten cases are reported in the English-language literature. To date there is no definite proof of the origin of this tumor. Both mesothelial and fibroblas-tic genesis has been postulated. The monoclonal antibody CD 34 has recently been used for the characterization of SFT. SFT would appear to be histogenetically related to a CD 34 - positive fibroblastic stem cell. A 61-year-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
2
18

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 14 publications
1
28
2
18
Order By: Relevance
“…Only 42 cases of primitive liver SFT have been described, and only 4 of those were classified as malignant [1]. Although there are no close correlations between morphology and malignant behavior, large size (more than 5 or 10 cm), sessile lesions, infiltrative margins, hypercellularity, nuclear pleomorphism, cytologic atypia, necrosis or hemorrhage and an increased mitotic index (more than 4 mitoses in 10 HPFs) have been described in malignant SFTs [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Only 42 cases of primitive liver SFT have been described, and only 4 of those were classified as malignant [1]. Although there are no close correlations between morphology and malignant behavior, large size (more than 5 or 10 cm), sessile lesions, infiltrative margins, hypercellularity, nuclear pleomorphism, cytologic atypia, necrosis or hemorrhage and an increased mitotic index (more than 4 mitoses in 10 HPFs) have been described in malignant SFTs [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, association to hypoglycemia, possibly mediated by insulin growth factors, has been described in 4% to 10% of cases (7)(8)(9)(10), more often in SFT arising from peritoneum.…”
Section: Introductionmentioning
confidence: 99%
“…M21(i(14q)) i(14)(q10) M22(der(15)) add(15)(?::pter-q24::?) M23 (der(15;22)) der (15) Characterisation of a novel cell line (CSQT-2) T Wang et al Moreover, as is well-known, the theory of cancer stem cells argues that a cancer mass is built up by a relatively tiny portion of the total tumour, called cancer stem cells or TIC (Guglielmi et al, 1998;Bansal and Banerjee, 2009;Kawasaki et al, 2009;Tu et al, 2009). The previous research on HCC TICs found that we could separate or enrich HCC TICs through specific staining for cell surface markers, such as CD133, CD90 and EpCAM (Yang et al, 2008a, b;Yamashita et al, 2009;Yeh et al, 2009;Yoshikawa et al, 2009;Zhu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%